On the Ramsey numbers r(K2,n-1, K2,n) and r(K2,n, K2,n) - Lortz, Roland; Mengersen, Ingrid (Utilitas Mathematica, 2002)
An upper bound on the Ramsey number r(K2,n-1, K2,n) is presented. By constructing a special (K2,n-1, K2,n)4n-5-coloring from symmetric Hadamard matrices we prove that this bound matches the exact value of r(K2,n-1, K2,n) in infinitely many cases including all but four n ≤ 58. Moreover, some results on the diagonal Ramsey number r(K2,n, K2,n) extending those in [1] are given.